Medicinal Plant Diversity in Newly Reported Sacred Grove of Pithoragarh District, Uttarakhand - Singh, Harsh; Singh, Pushpi; Husain, Tariq (Indian Forester, 2011)
Sacred groves are small or large patches of vegetation dedication to local ancestor or deities and often represented climax vegetation of the region. Haat Kali sacred grove. which is newly reported, is one such example in having important medicinal plants and many non - medicinal plants. The grove covers an area of 1.7 approximately and consists of 22 species belonging to 22 genera and 22 families of medicinal plants which are not found in the other parts of the district at the same altitude of 1750 ro. It is important to conserve this type of grove in having maximum genetic diversity of medicinal plants by strong steps.